Investigating entrepreneurship as the nexus to mainstreaming the micro enterprise informal sector: A case study of blue chip companies in the Nairobi Securities Exchange and government organizations tasked with mainstreaming the micro enterprise jua kali sector in Kenya - Addero-Radier, B (Research of GSB, 2017)
Background The process of mainstreaming the informal sector into the formal sector in Kenya has been considered and evaluated from as early as the 1970 as a means of poverty reduction and job creation. Information available on mainstreaming from the formal sector and government in Kenya indicate that both these sectors appreciate the value of mainstreaming the informal sector, however both parties have been unable to successfully mainstream the informal sector into the formal sector more than 40 years on. The relationship between the three sectors has also been reviewed and both the formal and government sector are cognizant of the need to create an enabling environment that would foster the mainstreaming process through an appropriate legal and regulatory framework. Methods The study follows a case study approach underpinned by an interpretive foundation. An extensive published literature, secondary data on the informal sector and grey-literature search on mainstreaming was conducted between 2006 and 2010. Between 2007 and 2008 a survey was conducted a threepronged approach to allow independent surveys of the informal sector as represented by the three largest jua kali (Kiswahili words for 'hot sun' which signifies outdoor exposure characterising the informal sector trade) markets in Kenya, namely Gikomba, Kariobangi and Kawangware. The government institutions mandated with various responsibilities for the informal sector as represented by blue chip companies on the Nairobi Stock Exchange (NSE), today known as The Nairobi Securities Exchange and the government sector represents the formal sector. Stringent criteria were applied to select the sample data where random sampling was used for the informal sector in the three named markets. Survey sample size for the informal sector was 539. The survey was conducted between 2007-2008. The survey for the selected blue chip companies was conducted in 2008. The findings from the survey precipitated the need to conduct a survey within the government sector, specifically with the government bodies and ministries with the mandate to facilitate the development of the jua kali sector. Face to face interviews using open-ended questionnaires was used to collect the data and identify opportunities for mainstreaming and integration amongst the three sectors. The effects of this association was interrogated and evaluated in order to identify opportunities that can establish a sustainable and long-term mainstreaming process for the informal sector in Kenya.